2018
DOI: 10.9738/intsurg-d-18-00031.1
|View full text |Cite
|
Sign up to set email alerts
|

Demodex Mite Infections in Ophthalmic Patients on Indonesian Islands: The ICS Humanitarian Aid Report

Abstract: Objective: Demodex is the most common external human parasite. It has been suggested that the Demodex infection may be associated with malnutrition, nutritional deficiencies, reduced immunity, and poor hygiene. The patients who benefitted from humanitarian aid

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
1
0
0
Order By: Relevance
“…However, it is recommended to study the changes of humidity and pH of the skin and their effects on the mites. Previous studies on the relationship between Demodex prevalence and location of residency are relatively scarce; however, the results of this study are in agreement with few previous studies where no significant difference was found between types of residency [14,22,26]; however, it is in disagreement with studies that reported higher rates in rural areas [15]. Perhaps this difference in findings is due to the fact that patients in urban areas are more likely to use artificial lipids and cosmetics, which may have had an effect on the prevalence rates of these mites when compared to rural areas.…”
supporting
confidence: 92%
“…However, it is recommended to study the changes of humidity and pH of the skin and their effects on the mites. Previous studies on the relationship between Demodex prevalence and location of residency are relatively scarce; however, the results of this study are in agreement with few previous studies where no significant difference was found between types of residency [14,22,26]; however, it is in disagreement with studies that reported higher rates in rural areas [15]. Perhaps this difference in findings is due to the fact that patients in urban areas are more likely to use artificial lipids and cosmetics, which may have had an effect on the prevalence rates of these mites when compared to rural areas.…”
supporting
confidence: 92%